THE ROLE OF PHYSICAL EDUCATION TEACHERS IN IMPLEMENTING ACTIVE LEARNING STRATEGIES IN LIGHT OF CERTAIN VARIABLES FROM THEIR PERSPECTIVE IN AL-ANBAR GOVERNORATE - Haider Ahmed Shihab (Proximus Journal Publishing, 2025)
In light of specific factors from their point of view, the study sought to determine the degree to which male and female physical education instructors use the active learning technique. 142 secondary school teachers from the Ramadi district made up the study sample. The researcher used a questionnaire with 55 questions to accomplish the study's goals. The study suggested that secondary school physical education instructors keep including the active learning technique in their teaching methods since the results demonstrated the importance of doing so
Keywords: Teachers; Active Learning Strategies; Physical Education